The Kenyan indigenous languages and the mass media: Challenges and opportunities - Orao, James (Stellenbosch Papers in Linguistics Plus, 2012)
While it is officially recognized that Kenya is a multilingual state, necessary mechanisms for the effective management of this diversity have not been effected. With English and Kiswahili occupying the "official language" positions, the other more than forty local languages are excluded and have no "official" recognition. The relatively recent development of vernacular mass media has not only provided an impetus for the re-examination of the status of indigenous languages in Kenya, it has also brought with it opportunities and challenges which are yet to be critically examined. Many questions are being raised regarding the status of the vernacular mass media, their possible influence on the local languages, the possible challenges they raise within the national language policy, and their role in the public domain. This paper addresses these questions and examines the relationship between the vernacular mass media and the Kenyan indigenous languages. Keywords: indigenous languages, language management, vernacular mass media